Development of a robotic additive manufacturing cell based on laser metal deposition using wire - Betancourth, Brayan Stiven Figueroa (2025)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2025.